Tactics of translating official parts of speech from Russian into Arabic - Mamdooh, Huda Zain AL-Abdeen; CHALLOOB, MAHMOOD GHAZI (Al-Adab Journal, 2022)
Undoubtedly, the translation of official parts of speech from Russian into Arabic is not an easy task, according to most people. Both languages have different patterns and different word order. This article is devoted to the tactics of translating official parts of speech from Russian into Arabic. The article attempts to present ways of translating official parts of speech from Russian into Arabic. Besides. The article analyzes the features of the translation of official parts of speech from Russian into Arabic and identifies some tactics of their translation. Further, the article provides the correct solutions to translation problems in relation to the translation of official parts of speech from Russian into Arabic. Translation is indispensable in our daily life, because it is an important intermediary of human communication. Nowadays, the importance of translation is increasing due to the constant development of trade, science, culture, technology, and so on. Translation is a field of contrastive linguistics, since it is associated with at least two languages and their cultures. This is the process of transmitting a message by switching from one language system to another. In other words, it is a method used to transfer and / or transform the meaning of a written term or text of the source language into the target language using words that have direct equivalence, new words or terms, foreign words written in the target language, or using foreign words to match the pronunciation of the language being studied.